2021
DOI: 10.1038/s41467-020-20562-w
|View full text |Cite
|
Sign up to set email alerts
|

Giant isotropic magneto-thermal conductivity of metallic spin liquid candidate Pr2Ir2O7 with quantum criticality

Abstract: Spin liquids are exotic states with no spontaneous symmetry breaking down to zero-temperature because of the highly entangled and fluctuating spins in frustrated systems. Exotic excitations like magnetic monopoles, visons, and photons may emerge from quantum spin ice states, a special kind of spin liquids in pyrochlore lattices. These materials usually are insulators, with an exception of the pyrochlore iridate Pr2Ir2O7, which was proposed as a metallic spin liquid located at a zero-field quantum critical poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…However, promising three-dimensional (3D) QSL candidates are still rare since higher dimensionality suppresses the quantum fluctuations. Hyperkagome Na 4 Ir 3 O 8 [25][26][27] and pyrochlore Pr 2 Ir 2 O 7 [28][29][30][31] are the only two representative 3D QSL candidates and have been the subject of extensive studies. Even if the absence of magnetic order and spin dynamics are found, it is not sufficient to claim a QSL material, since those observations can be explained by other mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, promising three-dimensional (3D) QSL candidates are still rare since higher dimensionality suppresses the quantum fluctuations. Hyperkagome Na 4 Ir 3 O 8 [25][26][27] and pyrochlore Pr 2 Ir 2 O 7 [28][29][30][31] are the only two representative 3D QSL candidates and have been the subject of extensive studies. Even if the absence of magnetic order and spin dynamics are found, it is not sufficient to claim a QSL material, since those observations can be explained by other mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This material is suggested to be a Luttinger semimetal, that is to host a quadratic band touching at the Γ point of the Brillouin zone (BZ) [6]. Early on it was suggested to be a chiral metallic spin liquid [5,[7][8][9]. We found that a comparative study of their phonon spectra can reveal information of the coupling of the lattice to magnetic and electronic degrees of freedom which is difficult to identify otherwise.…”
Section: Introductionmentioning
confidence: 98%
“…However, promising three-dimensional (3D) QSL candidates are still rare since higher dimensionality suppresses the quantum fluctuations. Hyperkagome Na 4 Ir 3 O 8 [25][26][27] and pyrochlore Pr 2 Ir 2 O 7 [28][29][30][31] are two representative 3D QSL candidates and have been the subject of extensive studies.…”
Section: Introductionmentioning
confidence: 99%